Desistance in Context: Understanding the Effects of Subculture on the Desistance Process During Reintegration - Bell, Shane (The British journal of criminology, 2021)
Despite a growth in desistance research, our understanding of how local external factors may affect the desistance process as people transition from prison to society remains limited. Drawing on qualitative data from two neighbourhoods in Northern Ireland, it is argued that subcultural factors in neighbourhoods can play a key role in influencing desistance during reintegration by shaping the opportunities that individuals have to access, use and sell drugs, their experiences of social integration/exclusion and processes of surveillance and collective efficacy. It is argued that there is a need to better incorporate the effects of local external factors, including subcultural norms and values, into existing desistance theories if we are to fully understand how neighbourhood context can affect desistance during reintegration.